Kinerja Kelompok Tani Terhadap Pengembangan Komoditi Padi Pada Program Perluasan Areal Tanam Di Kecamatan Terara - Sahwil; Anwar, Muhammad; Rini Endang Prasetyowati (MAHATANI: Jurnal Agribisnis (Agribusiness and Agricultural Economics Journal), 2025)
The purpose of the study was to determine the effect of farmer group performance on the development of rice commodities in the Planting Area Expansion Program with Pumping Scheme in Terara District. Descriptive methods with quantitative and qualitative approaches were used to achieve the objectives, with the location in Terara District, East Lombok Regency, which was selected purposively. Respondents were 75 farmers who were members of farmer groups actively participating in the PAT Program with Pumping Scheme for paddy rice commodities. Data were obtained using a questionnaire instrument and analyzed using descriptive Likert scoring and multiple linear functions. The results showed that the performance components of farmer groups simultaneously influenced the development of rice commodities in the Planting Area Expansion Program with Pumping Scheme in Terara District. Partially, there were no components that had a significant effect, there were three components of independent variables that supported the PAT program, namely institutional variables (X1), economic (X2), social (X3), and there were two independent variables whose relationships were not in the same direction but had a significant effect, namely the accessibility variable (X4) and government policy (X5)